2018
DOI: 10.1063/1.5042665
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic analysis of deuterated water via single- and double-pulse laser-induced breakdown spectroscopy

Abstract: Spatial segregation of species presents one of the main challenges in quantitative spectroscopy of laser-produced plasmas, as it may lead to overestimation of the concentration of the heavier species. Analytical capabilities can also be affected by excessive Stark broadening at atmospheric pressure, hindering the ability to spectrally resolve closely spaced spectral lines, such as those belonging to isotopes of the same element. We present an experimental and modeling study of the segregation of species and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For light elements, the LAMIS technique is extremely powerful for obtaining isotope ratio information alongside the elemental composition of materials and has application to nuclear processes where light elements and their isotopes are to be measured like H and B, for example. 344,360 For heavy elements such as the major actinides (e.g., U and Pu), the development of LA plasma spectroscopy techniques capable of accurately resolving small atomic isotope shifts is necessary. One method for improving the ability to resolve isotope shifts in LIBS measurement is increasing the resolving power of the spectrometer; the use of large, high resolvingpower spectrometers has been a constant in isotopically resolved measurements of atomic spectra.…”
Section: Laser Ablation Molecular Isotopic Spectrometry (Lamis)mentioning
confidence: 99%
See 2 more Smart Citations
“…For light elements, the LAMIS technique is extremely powerful for obtaining isotope ratio information alongside the elemental composition of materials and has application to nuclear processes where light elements and their isotopes are to be measured like H and B, for example. 344,360 For heavy elements such as the major actinides (e.g., U and Pu), the development of LA plasma spectroscopy techniques capable of accurately resolving small atomic isotope shifts is necessary. One method for improving the ability to resolve isotope shifts in LIBS measurement is increasing the resolving power of the spectrometer; the use of large, high resolvingpower spectrometers has been a constant in isotopically resolved measurements of atomic spectra.…”
Section: Laser Ablation Molecular Isotopic Spectrometry (Lamis)mentioning
confidence: 99%
“…It was noted by the authors that the Doppler and Stark shift effects were observed to shift the location of the absorption feature in the self-reversed emission line; thus, matrix-matched samples must be used to construct a calibration curve as these effects depend on changes of the plasma conditions that the matrix composition strongly influences. Burger et al 344 investigated the spatiotemporal distribution of the D α and H α emission following single and double pulse LA of a frozen deuterated water sample. The researchers focused their investigation on the LA parameters that lead to reduced Stark broadening, which was reduced for DP-LIBS, and resolution of the Balmer emission line to resolve the H α and D α emission simultaneously for standoff detection in support of nuclear security applications.…”
Section: Laser-induced Breakdown Spectroscopy (Libs) Throughout the Nfcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with its application for the detection of liquid and solid samples, there are few publications on the detection of gaseous samples, especially in-situ detection under atmospheric pressure, because the low density of gas samples makes it difficult to observe the characteristic lines of the target element in the emission spectra. With the development of laser techniques and the theory of light-matter interaction, some novel LIBS techniques, such as femtosecond LIBS and dual-pulse LIBS, [39][40][41][42] have been applied to improve the intensity and stability of the spectral signal. More and more studies are currently being carried out to improve the performance of the LIBS detection of gas, and the LIBS technique is playing an increasingly important role in the detection of atmospheric environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] So far, LIBS has been successfully demonstrated for discriminating various nuclear-related materials isotopes such as U ( 235 U/ 238 U), 2,10 Pu ( 239 Pu/ 240 Pu), 14,15 Li ( 6 Li/ 7 Li), 12,16 and H ( 1 H/ 2 H). [17][18][19][20] LIBS has the ability to provide spatially resolved maps of H isotopes and perform depth proling. In particular, when an ultrafast laser is used for ablation, improved spatial mapping and precision depth proling capabilities can result, owing to its limited heat-affected zone in comparison to nanosecond pulsed lasers.…”
mentioning
confidence: 99%